2013
DOI: 10.1121/1.4812882
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamics of the acoustic vaporization of phase-change microdroplets

Abstract: Acoustically sensitive emulsions are a promising tool for medical applications such as localized drug delivery. The physical mechanisms underlying the ultrasound-triggered nucleation and subsequent vaporization of these phase-change emulsions are largely unexplored. Here, the acoustic vaporization of individual micron-sized perfluoropentane (PFP) droplets is studied at a nanoseconds timescale. Highly diluted emulsions of PFP-in-water and oil-in-PFP-in-water droplets, ranging from 3.5 to 11 μm in radius, were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 38 publications
3
56
1
Order By: Relevance
“…There is also an unexplained decrease of the threshold pressure with increasing size of the droplets (20,21). Finally, ultrahigh-speed imaging has allowed for the construction of spatial and temporal nucleation maps (22). This showed that the nucleation spots inside the droplets were highly localized for some bubbles, whereas other bubbles had nucleation spots at random positions throughout the droplet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an unexplained decrease of the threshold pressure with increasing size of the droplets (20,21). Finally, ultrahigh-speed imaging has allowed for the construction of spatial and temporal nucleation maps (22). This showed that the nucleation spots inside the droplets were highly localized for some bubbles, whereas other bubbles had nucleation spots at random positions throughout the droplet.…”
mentioning
confidence: 99%
“…This showed that the nucleation spots inside the droplets were highly localized for some bubbles, whereas other bubbles had nucleation spots at random positions throughout the droplet. The authors suggested that the location of such spots may be a function of the droplet size (22). The authors also pointed out that temporally the initiation of the nucleation is shifted toward the end of the rarefactional half cycle of the ultrasound pulse.…”
mentioning
confidence: 99%
“…7.5 it can be observed that the nucleation process initiated by the ultrasound exposure is not instantaneous in time, as was also shown before 183 . Fig.…”
Section: 5supporting
confidence: 69%
“…Nucleated droplets are marked by the red-dotted circles. It is observed that the nucleation bubble grows rapidly under acoustic forcing 183 . When the ultrasound is turned of, the bubble rapidly decreases in size.…”
Section: 5mentioning
confidence: 99%
“…Experiments in either fluid were conducted separately, and small differences in focal alignment between experiments (less than a microsecond), while not affecting the peak pressure, render the exact phase of ultrasound in each frame difficult to ascertain. Indeed, a novel cross-correlation technique to do so by employing the bubble as a pressure sensor was recently demonstrated (Shpak et al, 2013), however, this was not attempted in the present study. Figure 6 summarizes the size dependent results for all the microbubbles insonicated at either (a) 100 or (b) 250 kPa in both 1 (circles) and 4 cP (triangles) fluid.…”
Section: Resultsmentioning
confidence: 98%